Partners in progress: Collaborative investments driving the scaling of community-based breeding programs in Ethiopia - Tolemariam, Taye; Agabez, Solomon; Getachew, Tesfaye; Haile, Aynalem; Rekik, Mourad; Belay, Berhanu; Rischkowsky, Barbara (International Livestock Research Institute, 2024)
In recognition of its importance for the smallholder farmers and achieving their core missions, numerous institutions in Ethiopia, including federal universities, regional and federal research centres, as well as governmental and non-governmental organizations, have dedicated considerable time and resources to implementing the Community-Based Breeding Program (CBBP) for small ruminants. Thus, the total budget of USD 1,604,253, USD 1,039,644,69 (65%) provided by the research institutes, USD 469,264.52 (29%) coming from the universities and USD 95,349.97 (6%) contributed by the community, were invested for CBBP implementation (Table 1). This difference in investment between the research system and universities is due to the research system starting the CBBP implementation earlier than the universities. The significant investment from various institutions and communities demonstrates a commitment to expanding the CBBP for small ruminants, which is crucial for the program’s sustainability and enhancing the productivity of the animals.